The genus Gymnospermium (Berberidaceae) in Italy: identity and relationships of the populations at the western limit of the genus range - Rosati, Leonardo; Coppi, Andrea; Farris, Emmanuele; Fascetti, Simonetta; Becca, Giovanna; Peregrym, Mykyta; Tan, Kit; Selvi, Federico (Plant biosystems, 2019)
Gymnospermium is a small genus of 7-12 taxa subject to diverging taxonomic treatments and distributed from east China to the Balkans. The recent discovery of Gymnospermium in the S-Apennines posed questions about origin and identity. Accordingly, we performed a systematic investigation by means of morphological, karyological and molecular tools. All populations were diploid with 2n = 14 as for the Balkan G. scipetarum (incl. G. maloi), and also morphology suggested a close affinity to the latter. However, the Italian populations differed from typical G. scipetarum by the lower stamen:petal length and style:carpel length. By including all European and most Asian taxa in a phylogenetic analysis, we shed new light into the species-level relationships in this genus. In the combined ITS-trnL-F phylogeny, two major clades were retrieved. One included the central Asian and eastern European taxa plus the Greek endemic G. peloponnesiacum sister to G. odessanum, and one the Balkan and Apennine populations. Such findings further corroborated that the Apennine plant belong to G. scipetarum. The native status of the Italian population is supported by exclusive SNPs in both ITS1 and trnL-F sequences. Along with morphological evidence, this allows to refer it to the new subspecies G. scipetarum subsp. eddae.